Hydraulic Assessment of Grassed Swale as Bioengineered Channel - Muhammad, M.M.; Yusof, K.W.; Mustafa, M.R.; Ghani, A.Ab. (2016)
This paper evaluates the suitability of a grassed swale for channel stabilization against erosion, as an alternative to concrete drainage systems.To achieve this objective, hourly flow measurements due to different rainfall events were made along 10m length of the grassed swale. The data collected were cross sections, grass geometry, flow depth and velocity. Rating curves, velocity distributions, stage and velocity – Manning’s resistance relationships were developed, respectively, with correlation coefficients, R2, mostly above 70%. Also, the centerline velocity of grassed swale was determined to range from 0.05 to 0.76 m/s. The shear stresses fall between 3.47 to 6.59 N/m2 both on bed and bank of the swale. Comparing the velocity and shear stresses values with standard charts, it was found that all values are within the allowable limit. Thus, the relationships developed would be suitable for designing an erosion resistant grassed swale based on Malaysia climate conditions and alike.